Urethral Mucosa Prolapse in an 18-Year-Old Adolescent - Akadiri Olumide; Ajenifuja Kayode Olusegun; Bakare Babatola (Hindawi Limited, 2013)
Urethra mucosa prolapse is a benign condition in which there is a circular protrusion of the distal urethra through the external urethra meatus. It is more commonly seen in prepubertal black girls and postmenopausal white women. It is rare in the reproductive age group. This case describes the presentation and management of an 18-year-old adolescent with urethra mucosa prolapse.